2000
DOI: 10.1088/0022-3727/33/24/316
|View full text |Cite
|
Sign up to set email alerts
|

Use of photoacoustic effect for the detection of phase transitions in liquid crystal mixtures

Abstract: Abstract. We report on a laser induced photoacoustic study of the nematic-to-isotropic transition in certain commercial nematic liquid crystal mixtures, namely BL001, BL002, BL032 and BL035. A simple analysis of the experimental data using the Rosencwaig-Gersho theory shows that the heat capacities of all these compounds exhibit a sharp peak as the temperature of the sample is varied across the transition region. Also, substantial differences in the photoacoustic signal amplitudes in nematic and isotropic phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…But the measured values of the thermal effusivity fall in the range of several other liquid crystals ͑calculated from the heat capacity and the thermal conductivity data͒ in the nematic phase. 2,13,15,16 Also, the experimental calibration using water and glycerol ensures high accuracy for the present method.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…But the measured values of the thermal effusivity fall in the range of several other liquid crystals ͑calculated from the heat capacity and the thermal conductivity data͒ in the nematic phase. 2,13,15,16 Also, the experimental calibration using water and glycerol ensures high accuracy for the present method.…”
Section: Resultsmentioning
confidence: 89%
“…This method has also been applied for the thermal characterization of liquid crystals. [12][13][14][15][16] Very recently, N. A. George et al demonstrated the use of an open PA cell configuration for the thermal characterization of certain comb-shaped polymers. 12 The principle of the PA effect is based on the light-induced heat release and consequent acoustic generation from a material when it is irradiated with a modulated optical radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Sound is produced when a periodic light beam is incident on any sample surface and this effect is called the ‘photoacoustic effect’. 1–3 Photoacoustic spectroscopy (PAS) is a novel spectroscopy technique used to measure optical and thermal properties of materials of any phase (solid, liquid or gas) 4 . It has two working modes, (i) varying frequency mode where PA signal is recorded at different chopping frequencies for any selected excitation wavelength and (ii) fixed frequency mode where PA signal is measured against different excitation wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…Rosencwaig and Gersho had first published the theoretical model for explanation of the PA effect in condensed media [28]. Nowa-days PA spectroscopy can effectively be used to study any state of the samples like solid, liquid or gas [29,30]. In PA spectroscopy periodic light absorption produces periodic heat generation which finally generates periodic air fluctuations in closed small air volume.…”
Section: Introductionmentioning
confidence: 99%